Are Household Water Purification Devices Useful to Improve the Physical Chemical and Microbial Quality of the feed Water? Case Study: Bandar Abbas South of Iran - Mojtaba Afsharnia (Journal of Global Pharma Technology, 2017)
Part of the Bandar Abbas population in southern Iran, in order to access to better water quality than municipal tap water systems, use household water purification devices. The aim of this study was to determine to what extent these devices are effective in improving the quality and the efficiency are desirable for the production of water quality. This cross-sectional study that was conducted in a six-month period time in 2015 in Bandar Abbas. A total of 30 samples of water from various home water purification apparatuses were sampled and tested for hardness, alkalinity, pH, total dissolved solids (TDS) and electrical conductivity (EC), turbidity and MPN was performed on the samples. Statistical analysis was performed using SPSS version 19 and statistical tests ANOVA and Pearson correlation test. The efficiency of the apparatuses to reduce turbidity, hardness, alkalinity, Na, K and Cl, respectively were 45.9, 39, 22.3, 30.6, 34.9 and 53 percent, and in reduce of TDS and EC respectively were 37.5 and 59 percent. The devices ability to change the pH of water was low and negative; (-5.8 percent). In 26.6% of influent samples, microbial contamination was detected, which in all mentioned cases, the microbial contaminated were showed in effluent samples. In general, the use of these devices was not necessarily lead to improved water quality. After working the 12-month period significantly decreased efficiency. The number of treatment stages did not impact in device efficiency improvement.Keywords: Water treatment, Purification devices, Water quality, Chemical quality.